Popular education in Mental Health: experience report - Carneiro, Allann da Cunha; Oliveira, Ana Carolina Moreira; Santos, Mariane Marques de Souza; Alves, Mirian dos Santos; Casais, Noêmia de Aragão; Santos, Ailton da Silva (Saúde e Sociedade, 2010)
This article presents an experience of popular education in mental health in the context of the Psychiatric Reform. Such experience occurred in the district of Pernambués, territory of the Centro de Atenção Psicossocial Álcool e Outras Drogas (Center for Psychosocial Assistance Alcohol and Other Drugs), located in the city of Salvador, state of Bahia. This center is the field for the practice of interns of the Mental Health Nucleus of the Multiprofessional Health Internship of Universidade do Estado da Bahia (UNEB - University of the State of Bahia). Such strategy was enabled by the organization of community forums involving many social actors. In this work, we used the methodology of experience systematization proposed by Holliday. By giving voice and time to each speaker/participant, in equal levels of knowledge and power, the popular education strategy allowed the people involved in this process to politically organize themselves. In addition, these people participated in the collective construction of new knowledge and practices in the mental health area, in keeping with the valuation of life in its multiplicity.